Efficacy and safety of traditional Chinese medicine in the treatment of menopause-like syndrome for breast cancer survivors: a systematic review and meta-analysis - Wang, Runxi; Wang, Yan; Fang, Liyuan; Xie, Yi; Yang, Shuhan; Liu, Suying; Fang, Yuhang; Zhang, Ying (BMC cancer, 2024)
In recent years, breast cancer (BC) incidence and mortality have been the highest in females. Menopause-like syndrome (MLS), arising from hypoestrogenism caused by endocrine therapy, significantly affects the quality of life for females. Traditional Chinese Medicine (TCM) has advantages in ameliorating MLS, but the efficacy of TCM in patients with BC has not been systematically evaluated. A comprehensive search was performed on PubMed, Web of Science, Embase, Ovid, Cochrane Library, China National Knowledge Infrastructure, Wanfang database, Chinese Scientific Journals Database, and Clinical Trial Registry from inception to September 4, 2023. The Cochrane Risk of Bias assessment tool was used for the quality evaluation of the randomized controlled trials (RCTs). Review Manager 5.4 software was used for statistical analysis, and the Grading of Recommendations Assessment, Development, and Evaluation was used for quality evaluation of the synthesized evidence. This review included 42 studies involving 3112 female patients with BC. The results showed that the TCM group was better at decreasing the Kupperman Menopausal Index (KMI) scores (standardized MD, SMD = - 1.84, 95% confidence interval, CI [- 2.21--1.46], Z = 9.63, P < 0.00001). Regarding the main symptoms of MLS, the TCM groups could significantly decrease the scores of hot flashes and night sweats (SMD = - 0.68, 95% CI [- 1.1--0.27], Z = 3.24, P = 0.001), paraesthesia (SMD = - 0.48, 95% CI [- 0.74--0.21], Z = 3.53, P = 0.0004), osteoarthralgia (SMD = - 0.41, 95% CI [- 0.6-0.21], Z = 4.09, P < 0.0001), anxiety (MD = - 0.85, 95% CI [- 1.13, - 0.58], Z = 6.08, P < 0.00001) and insomnia (MD = - 0.61, 95% CI [- 0.8, - 0.43], Z = 6.51, P < 0.00001). TCM can effectively improve the symptoms of MLS in patients with BC. Moreover, TCM could improve the objective response rate (ORR) by 50% (RR = 1.5, 95% CI [1.37-1.64], Z = 9.01, P < 0.00001). Follicle-stimulating hormone (FSH) and oestradiol (E ) had no significant difference compared with the control group (p = 0.81 and p = 0.87), and luteinizing hormone (LH) in the TCM group decreased significantly (MD = - 0.99, 95% CI [- 1.38, - 0.5], Z = 5.01, P < 0.00001). This means that the use of TCM does not negatively affect endocrine therapy and may even have a synergistic effect. The incidence of adverse events (AEs) was lower in the TCM groups than in the control groups. The meta-analysis stated that TCM could better improve the MLS of patients, alleviate related symptoms, and did not increase adverse drug reactions in BC survivors. This review brings more attention to MLS, and the present findings shed light on the potential applications of TCM in the treatment of MLS in BC survivors.